Omride Architecture at the Town of Nebo - Edwards, Steven ca. 20./21. Jh. (Zeitschrift des Deutschen Palästina-Vereins, 2019)
This article examines the Iron Age remains at Ḫirbet el-Muḫayyiṭ (ancient Nebo), suggesting that they exhibit several features consistent with Omride architecture observed at other sites in northern Moab, especially Ḫirbet el-Mudēyine eṯ-Ṯemed and Ḫirbet ʿAṭārūz. The elongated compound is built on an elevated platform fortified by a casemate wall and rock-cut moat. It is also supported by a nearby watchtower at Ruǧm el-Muḫayyiṭ. The association of fortified compounds with watchtowers appears to be a feature of Omride sites in northern Moab.